Peran Orang Tua dalam Pendidikan Akhlak Anak Usia Dini: (Studi Kasus Guru Berkeluarga di Lingkungan Pondok Pesantren Al-Amien Prenduan) - Rindatus Jaujah; Luthfatul Qibtiyah (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2021)
This research aim to describe the role of parents in early childhood moral education, and describe the supporting and inhibiting factors in the implementation of early childhood moral education. This study is a qualitative research with case research. data collection methods used are interview and observation. The subject of this study are four pople, with criterias are mothers who become teachers and have early childhood. Data analysis used is Miles and Huberman model, that are data reduction, data presentation and verification. Check data validity used is triangulation. The results showed that the role of mothers in early childhood moral education in Al-Amien Prenduan Islamic Boarding School environment are provide role model, supervision and advice. The supporting factor is environment which has positive impact. The inhibition factors are unflexibility of mother’s time, and different princip among family members and environment in early childhood moral education. Thus, moral education is important to implement since early age of children and demands parent’s sinergy.